Sengketa Pendaftaran Hak Milik Atas Tanah - Dewi Arnita Sari (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2020)
This journal aims to find about Ownership disputes land rights Related to land registration in Makassar city. The purpose of this study is : 1. to analyze the factors affecting the dispute over ownership of land that has been registered in Makassar. 2. to analyze how far the solutions are provided by the government in resolving ownership of land that has been registered.This research is descriptive research with empirical juridical approach method. Research method used is method by using primary and secondary data with data collecting technique that are interview and questionnaire. The population of this study are the employee office of the state land agency Makassar and public figure. Sample in this research is 30 respondents by using technique purposive sampling.The results of this study shownthat : (1). the factors affecting the dispute over ownership of land are Legal factors, law enforcement factors, facilities and infrastructure factors. (2). There are two solutions are provided by the government in resolving ownership of land, that was The national land agency facilitates to do mediation and Solutions through the judiciary, negotiations, and others Depending on the perpetrators leading in the direction of a good solution to them. Recommendation of this research is Government is expectedPlay an active role So that people did not have problems in dispute signs in the future, that is Increased administration to be more thorough in making land certificates In order to minimize the dispute. Developing the training in order to increase human resource of law enforcer, socialization to public can be held in great quantities and all of reinforced facility supplying so that all of factor whom can influence presence of proprietary right dispute for estate can be minimalized.Keyword : Ownership disputes land rights, land registration